2020
DOI: 10.1177/2049463720913289
|View full text |Cite
|
Sign up to set email alerts
|

The nociceptive flexion reflex: a scoping review and proposed standardized methodology for acquisition in those affected by chronic pain

Abstract: The nociceptive flexion reflex (NFR) is used in neurophysiological research as an objective measure of nociception. NFR thresholds are reduced in numerous chronic pain pathologies, which are indicative of common central hyperexcitability within conditions. However, variation exists in both the NFR assessment and determinants of NFR threshold among research groups. Our purpose was to provide a review of the recent literature to (a) confirm the NFR threshold’s efficacy in identifying those with chronic pain comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 62 publications
(227 reference statements)
0
1
0
Order By: Relevance
“…Yet, one reasonable approach is exploring the neurophysiological reflex behavior, as such reflexes in principle reflect the spinal excitation level based on distinct readouts such as response rates and magnitudes ( Sandrini et al, 2005 ). Reflex studies may either apply innocuous stimuli, e.g., to study the impact of SCI on the H-reflex ( Lee et al, 2005 ; Knikou, 2008 ; Gómez-Soriano et al, 2018 ; Pion et al, 2021 ), or noxious stimuli to assess the effect of injured sensorimotor pathways on nociceptive withdrawal—also referred to as nocifensive—reflexes ( Lim et al, 2011 ; Linde et al, 2021 ). Previous clinical and preclinical studies on the effect of SCI on nocifensive reflexes revealed motor hyperresponsiveness and enlarged reflex receptive fields (RRF) ( Dimitrijevic and Nathan, 1968 ; Andersen et al, 2004 ; Biurrun Manresa et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, one reasonable approach is exploring the neurophysiological reflex behavior, as such reflexes in principle reflect the spinal excitation level based on distinct readouts such as response rates and magnitudes ( Sandrini et al, 2005 ). Reflex studies may either apply innocuous stimuli, e.g., to study the impact of SCI on the H-reflex ( Lee et al, 2005 ; Knikou, 2008 ; Gómez-Soriano et al, 2018 ; Pion et al, 2021 ), or noxious stimuli to assess the effect of injured sensorimotor pathways on nociceptive withdrawal—also referred to as nocifensive—reflexes ( Lim et al, 2011 ; Linde et al, 2021 ). Previous clinical and preclinical studies on the effect of SCI on nocifensive reflexes revealed motor hyperresponsiveness and enlarged reflex receptive fields (RRF) ( Dimitrijevic and Nathan, 1968 ; Andersen et al, 2004 ; Biurrun Manresa et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%